Utilización de estrategias didácticas para potenciar la inteligencia corporal cinestésica, en los estudiantes de la escuela Cabo Minacho de la comunidad de Minas, del cantón Pucará de la provincia de Azuay - Ramón Nagua, Carlos Darwin (2014)
Kinesthetic body intelligence is a direct relationship between the body and the recreational and sporting activity, which enables the formation of the citizen through the development of skills and abilities such as physical - functional, motor, cognitive and sports, all of which It guarantees the presence of citizens with skills and attitudes of a positive nature prepared to meet the challenges of society in which he lives according transform qualitatively the same.